2015
DOI: 10.1016/j.ijsu.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Dramatically reduced incidence of vaginal cuff dehiscence in gynecologic patients undergoing endoscopic closure with barbed sutures: A retrospective cohort study

Abstract: Vaginal cuff separation subsequent to laparoscopic closure is a rare occurrence. While our incidence of VCD was low and comparable to other reported rates in the literature, we did not observe any cases of VCD following laparoscopic hysterectomy performed with barbed suture closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
1
31
2
2
Order By: Relevance
“…In the laparoscopic surgery arm (n = 483), vaginal cuff closure was performed with unidirectional or bidirectional barbed suture in 427 patients and cuff dehiscence was not reported in any of these cases. 26 In our study, we observed VCD in three patients (1.8%). Two of them were occurred at 75th and 122th days of surgery.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In the laparoscopic surgery arm (n = 483), vaginal cuff closure was performed with unidirectional or bidirectional barbed suture in 427 patients and cuff dehiscence was not reported in any of these cases. 26 In our study, we observed VCD in three patients (1.8%). Two of them were occurred at 75th and 122th days of surgery.…”
Section: Discussionsupporting
confidence: 49%
“…Of note, both were associated with sexual intercourse. Sexual intercourse is accepted as a risk factor for developing cuff dehiscence that has been previously published literature . However, cuff dehiscence had occurred 6th weeks after surgery and it seems that is not justified to attribute the VCD, solely to be sexual intercourse.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[20,21] Other studies indicate that the use of barbed sutures decreases the incidence of vaginal cuff dehiscence. [14,2224] …”
Section: Discussionmentioning
confidence: 99%
“…Rettenmaier ve ark. (20) çalışmalarında, barbed sütur ile kubbe süturasyonu sonrası dehisens riskinin daha az olduğunu bildirmiş-lerdir. Bu çalışmadaki hastalarda vajinal kubbe no:1 polyglactyn 910 ile kontinyu süture edilmiş ve hiçbir hastada vajinal kubbe dehisensi saptanmamıştır.…”
Section: Ahmad Ve Arkunclassified